The Role Of The Trainer In Developing The Skill Of Mental Perception Among High School Students And Its Effect On Improving Sports Performance Results - Benaissa , Mahrez; Ben Aki, Mhand Akli (sports creativity, 2025)
The research aims to recognize the role that trainers play in developing the skill of mental perception among high school students and its effect on improving the results of sport performance, and the sample included 15 coaches intentionally supervising sport high school students in Dararia, Algiers, and the researcher used the descriptive approach that befits this research In terms of achieving its goals, And then the results were processed by SPSS program which showed that there is a very big neglect of developing mental perception skill, and this matter is due to several reasons, including the lack of knowledge of the correct methods of how to develop this skill in athletes, so that the researcher concluded by making these recommendations : Mental skills training in general and mental perception in particular should be taken more seriously by the trainers, - Programming special configurations for trainers on mental perceptionn skill, - Mental perception training will develop learning skills more quickly than usual for sport high school students.